Earliest known spatial competition between stromatoporoids: evidence from the Upper Ordovician Xiazhen Formation of South China. (January 2020) - Jeon, Juwan; Liang, Kun; Lee, Mirinae; Kershaw, Stephen
Abstract: The earliest known interpreted spatial competition between two species of stromatoporoids, Clathrodictyon cf. C . mammillatum (Schmidt, 1858) and Labechia sp. is found in the Upper Ordovician Xiazhen Formation at Zhuzhai, South China. The interaction between these taxa was initiated by settlement of Labechia sp. on the surface of Clathrodictyon cf. C . mammillatum . Distortions of the intraskeletal elements of stromatoporoids represented by abnormally large, wide cysts and thick cyst plates in Labechia sp. are observed, along with zigzag crumpled distorted laminae and antagonistic behavior of the skeleton in Clathrodictyon cf. C . mammillatum, indicating syn-vivo interactions. The growth of Labechia sp. was terminated by the overgrowth of Clathrodictyon cf. C . mammillatum, possibly reflecting the ecological superiority of Clathrodictyon cf. C . mammillatum over Labechia sp. The observations are interpreted as competitive interaction between stromatoporoids that was most likely facultative, thus most likely occurring by chance, but the interaction allows assessment of different growth behaviors of the stromatoporoid species. Analysis of the interaction provides evidence to improve understanding of the paleoecology and growth behaviors of early stromatoporoids.